O livro do tempo: escritas e reescritas. Teatro greco-latino e sua receção, Vol. I - Maria do Céu Fialho (Classica Digitalia: Humanitas Supplementum - Estudos Monográficos, 2017)
These two volumes collect several studies about Greek and Latin theatre (I) and its reception (II). From An-tiquity, beside the analysis of specific texts, are considered aspects related with the evolution of the tragic and comic genres, their agents and their civic function. The reception studies (II) put together collaborators from a large geography and include a big number of case studies, mainly considering literature and theatre from the latin and iberoamerican world.